1996
DOI: 10.1007/bf02048261
|View full text |Cite
|
Sign up to set email alerts
|

Long-term analysis of the use of transanal rectal advancement flaps for complicated anorectal/vaginal fistulas

Abstract: TRAF is a safe technique for managing complicated anorectal and rectovaginal fistulas, including patients with Crohn's disease. Long-term follow-up is essential to accurately report recurrence rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
135
2
17

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(161 citation statements)
references
References 19 publications
7
135
2
17
Order By: Relevance
“…If the rectal mucosa is normal, ERAF can be used in Crohn fistulas as well. 31 A dermal island flap anoplasty (DIFA) is a procedure for resurfacing the anal canal in low anal strictures. Nelson and colleagues modified the procedure to cover the primary opening of the fistula after it was closed with absorbable sutures.…”
Section: Fistulotomy With Sphincterotomymentioning
confidence: 99%
“…If the rectal mucosa is normal, ERAF can be used in Crohn fistulas as well. 31 A dermal island flap anoplasty (DIFA) is a procedure for resurfacing the anal canal in low anal strictures. Nelson and colleagues modified the procedure to cover the primary opening of the fistula after it was closed with absorbable sutures.…”
Section: Fistulotomy With Sphincterotomymentioning
confidence: 99%
“…Various techniques have been described including fistulotomy [1][2][3][4], fistulectomy [5] and advancement flap procedures [6][7][8][9][10][11]. The results of fibrin glue treatment have been disappointing and the technique has largely been abandoned [12].…”
Section: Introductionmentioning
confidence: 99%
“…A summary of study characteristics is shown in Table  1, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75.…”
Section: Resultsmentioning
confidence: 99%
“…Eight retrospective30 37, 39 40, 42, 43, 44 46 and two prospective observational38 41 studies reported the outcome of mucosal advancement flaps in both Crohn's and cryptoglandular perianal fistulous disease. Of the 590 reported procedures, 204 were performed for Crohn's fistula.…”
Section: Resultsmentioning
confidence: 99%